Numerical modelling of river rehabilitation schemes - Swindale, Neil (1999)
This thesis is based on the application of hydraulic modelling techniques to the study of river rehabilitation schemes. River channelization and rehabilitation techniques are reviewed and the restoration of the River Idle is detailed. The rehabilitation of the Idle, consisting principally of the installation of a number of flow deflectors, forms the basis of the modelling work carried out.